HUBUNGAN ANTARA KECERDASAN EMOSIONAL DENGAN RESILIENSI PADA SISWA PENGHUNI RUMAH DAMAI - Setyowati, Ana; Hartati, Sri; Sawitri, Dian Ratna (Jurnal Psikologi, 2010)
Drug abuse in Indonesia is increasingly. Drug users not only adults, but adolescent and children. Many drug users who try to express the reasons as the cause of her fall on the drug early. Place of rehabilitation does not guarantee the student to complete recovery if they are not having their own intentions that he would work well. When he got out of rehabilitation, relapse risk can occur when students return along with fellow drug users. To solve problems and maintain health in a risk situation is the need for resilience. Resilience is the ability of individuals in overcoming life's challenges and maintain good health and energy so it can continue to live healthily. Students need emotional intelligence to develop resilience to survive in the face of challenges during the healing process so that they can return to normal life, and not experiencing relapse. The purpose this research is to know correlation emotional intelligence to resilience residents in House of Peace. This research was conducted on 16 resident in the House of Peace. The data collector used are two scales, that emotional intelligence scale (50 items, Î± = 0,946) and resilience scale (70 items, Î± = 0,964). Data analysis was performed using simple regression analysis. Results of data analysis showed positive correlation and significant between emotional intelligence to resilience ( = 0,801, p <0,05). The hypothesis of this research is received. The results showed that the effective contribution of emotional intelligence to resilience in this research equal to 64.1%.Keywords : resilience, emotional intelligence, residents House of PeacePermalink :